Association between IVF/ICSI treatment and preterm birth and major perinatal outcomes among dichorionic‐diamnionic twin pregnancies: A seven‐year retrospective cohort study. (5th October 2020) - Lin, Dongxin; Li, Pengsheng; Fan, Dazhi; Chen, Gengdong; Wu, Shuzhen; Ye, Shaoxin; Ma, Huiting; Rao, Jiaming; Zhou, Zixing; Zeng, Meng; Huang, Zheng; Guo, Xiaoling; et al.
Abstract: Introduction: This study aimed to evaluate the preterm birth and additional perinatal outcomes between spontaneous and in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) dichorionic‐diamnionic (DCDA) twin pregnancies. Material and methods: This retrospective cohort study was conducted in a tertiary university‐affiliated medical center. All women with DCDA twin pregnancies were considered for inclusion. The primary outcome of interest was preterm birth <37 weeks of gestation and secondary outcomes included spontaneous preterm birth, iatrogenic (induced) preterm birth, gestational diabetes mellitus, pregnancy‐induced hypertensive disorder, preeclampsia, preterm premature rupture of membranes (PPROM), intrahepatic cholestasis of pregnancy, placenta previa, neonatal intensive care unit (NICU) admission, birthweight discordance, small for gestational age, neonatal respiratory distress syndrome, ventilator support, and perinatal death and/or severe morbidity. These outcomes were compared between IVF/ICSI and spontaneous twin pregnancies. Multivariable logistic regressions were used to adjust for confounders. General estimated equation models were used to address intertwin correlation. Results: A total of 1297 twin pregnancies, including 213 spontaneous and 1084 IVF/ICSI DCDA pregnancies, met the inclusion criteria. Women with IVF/ICSI pregnancies were older and had higher body mass index, adherence with prenatal care and proportion of nulliparity. After adjustment for confounders, IVF/ICSI pregnancies were associated with a slight increase in preterm birth <37 weeks of gestation (adjusted odds ratio [aOR] 1.72; 95% CI 1.24‐2.39), iatrogenic preterm birth <37 weeks of gestation (aOR 1.41; 95% CI 1.00‐1.97) as well as NICU admission (aOR 1.34; 95% CI 1.00‐1.80). IVF/ICSI pregnancies were associated with a decrease in PPROM (aOR 0.64; 95% CI 0.42‐0.99). There were no differences between IVF/ICSI and spontaneous DCDA pregnancies in terms of spontaneous preterm birth, gestational diabetes mellitus, pregnancy‐induced hypertensive disorder, preeclampsia, intrahepatic cholestasis of pregnancy, placenta previa, birthweight discordance, small for gestational age, neonatal respiratory distress syndrome, ventilator support, and perinatal death and/or severe morbidity. Conclusions: IVF/ICSI DCDA twin pregnancies were associated with a slight increase in preterm birth <37 weeks of gestation, iatrogenic preterm birth <37 weeks of gestation, and NICU admission but with a decrease in PPROM. Other outcomes were comparable between IVF/ICSI and spontaneous DCDA twin pregnancies. Multicenter studies with adequate power remain warranted.